Experimental Investigation on Exhaust Noise Reduction Using Particulate Trap in Direct Injection (DI) Diesel Engine - Sundara Raman, R.; Sankara Narayanan, G.; Manoharan, N.; Sendilvelan, S. (Asian Journal of Engineering and Applied Technology, 2015)
Excessive pollution caused by engine emission has led to serious environmental degradation in the past three to five decades. Researchers worldwide are striving hard for reducing the emission from the engine. But the uses of dieselpowered vehicles are increasing day-by-day. The diesel engines have acquired much wider application than ever because of their main advantages of higher power and lower cost of the fuel. Although diesel exhaust is relatively clean with respect to unburnt hydrocarbons and carbon monoxide, it contains pollutants like particulate matter and oxides of nitrogen with greater exhaust noise. The paper reports on the control of the engine exhaust noise by a particulate trap for DI diesel engine. The experimental work comprises of design and development of the particulate trap for the given engine to control the exhaust noise level. The noise level reduction is also studied using a muffler. The reduction in noise level using particulate trap and muffler is experimentally investigated and compared. The noise level without particulate trap and muffler is 132 dB, with trap 116 dB, with muffler 125 dB. The percentage reduction in noise level is 12.5% with trap and is 9% with muffler.